SOCIAL-PSYCHOLOGICAL FACTORS OF THE FORMATION OF NATIONAL VALUES IN THE MIND OF STUDENTS (Universal International Scientific Journal, 2026)
This article analyzes the socio-psychological factors that influence the formation of national values ​​in the minds of young students. The expansion of the modern digital information environment has a significant impact on the worldview, social relations and value system of young people. Therefore, an in-depth study of the process of forming national values ​​in the minds of young people is of great scientific and social importance. The article analyzes the content of the concept of national values, their role in the process of youth socialization, and the main psychological and social factors that influence the formation of these values ​​in the minds of young students.
Keywords: national values, socio-psychological factors, socialization, national identity, digital environment, youth education, value system.